Single nanoparticle-based LSPR sensor for protein biomarker detection - Siu, Tenissa Jiarong (2015)
Research and development in the field of nanotechnology has been the topic of interest for the past few decades due to its vast and unique properties. These studies have brought its benefits to numerous fields including electrical, chemical, and optical as well as in the biomedical industries. In the biomedical industries, the optical properties of nanoparticles have seen an immense improvement for the purpose of eating, labeling and even drug delivery. These techniques are achievable due to the unique property of plasmonic nanoparticles, which is known as localized surface plasmon resonance (LSPR). This property is highly dependent on the structure, composition, size and shape of the nanoparticles. Therefore, this project aims to understand the relation between these two components. The focus of this study is based on the size and shape controlled synthesis of Au nanoshells predominantly by the seed mediated growth mechanism. UV-Vis spectrophotometry and scanning electron microscopy (SEM) are employed for the study and characterization of the nanoparticles through their maximum plasmonic absorbance and shape and size morphologies of the Au nanoshells formed, respectively.